Faktor-Faktor yang Mempengaruhi Minat Teknopreneur Melalui Motivasi pada Mahasiswa - Siti Marti'ah; Berta Dian Theodora (SAP (Susunan Artikel Pendidikan), 2020)
Entrepreneur day participants for 3 years in general have always increased in number, but unfortunately the number of participants in the technopreneurship business field is less than expected, in 2019 there were 3 participants out of 160 participants. This amount is relatively small so that a research is needed concerning on what factors can influence student’s motivation and interest in becoming a technopreneur in informatics students. This study used a quantitative approach to the path analysis method with independent variables, namely internal and external factors, entrepreneurship motivation as an intervention variable and technopreneur interest as the dependent variable. The research sample wad students who had taken entrepreneurship courses in the informatics study program as many as 300 students. The results showed that internal factors and external factors influenced entrepreneurial motivation by 36.4%. Entrepreneurial interest was directly influenced by internal factors and entrepreneurial motivation, while external factors did not directly affect the interests of technopreneur and needed to be through entrepreneurial motivation.